How Advertising Works: What Do We Really Know? - Vakratsas, Demetrios; Ambler, Tim (Journal of Marketing, 1999)
The authors review more than 250 journal articles and books to establish what is and should be known about how advertising affects the consumer—how it works. They first deduce a taxonomy of models, discuss the theoretical principles of each class of models, and summarize their empirical findings. They then synthesize five generalizations about how advertising works and propose directions for further research. Advertising effects are classified into intermediate effects, for example, on consumer beliefs and attitudes, and behavioral effects, which relate to purchasing behavior, for example, on brand choice. The generalizations suggest that there is little support for any hierarchy, in the sense of temporal sequence, of effects. The authors propose that advertising effects should be studied in a space, with affect, cognition, and experience as the three dimensions. Advertising's positioning in this space should be determined by context, which reflects advertising's goal diversity, product category, competition, other aspects of mix, stage of product life cycle, and target market.